Pola Hubungan Urbanisasi Dan Pertumbuhan Ekonomi Provinsi Maluku Utara - Yetty Yetty; Abdurahman Senuk; Chairulllah Amin; Elfira Salzabila (JFRES Journal of Fiscal and Regional Economy Studies, 2022)
This study aims to determine whether urbanization causes economic growth or economic growth causes urbanization. The analytical method uses Granger Causality to explore the pattern of the relationship between urbanization and economic growth. The results show that: Urbanization does not have a significant effect on economic growth. However, economic growth has a positive and significant effect on urbanization. The higher the level of economic growth, the level of urbanization is increasing in North Maluku Province. Improving economic conditions have caused rural communities to urbanize to areas that are considered worthy of being used as a source to get better welfare.